(untitled) (Archives of Clinical Psychiatry, 2012)
BACKGROUND: Depression, an important global health problem, negatively impacts the lives of individuals and their families beyond simply increasing the demand for health services. OBJECTIVE: To assess the prevalence of depression and associated mental health issues in individuals older than 14 years of age seeking primary care. METHODS: A cross-sectional study was conducted in three primary care units involved with the Catholic University of Pelotas. Depression, anxiety disorders, and suicide risk were assessed using the Mini International Neuropsychiatric Interview (MINI). Factors such as age, gender, solitary living, education, and psychoactive substance use were evaluated using a sociodemographic questionnaire. RESULTS: The overall prevalence of depression was 23.9% (n = 256). Depression was more prevalent in women with only 4-7 years of education, in women who belong to socioeconomic class D or E, in those who abuse or are dependent on alcohol, or in women who showed an anxiety disorder or suicide risk (p < 0.050). DISCUSSION: Based on these findings, we emphasize the integration of mental health care into primary care through diagnostic evaluations and treatment protocols that cover depression and its comorbidities.